PENGEMBANGAN MEDIA PEMBELAJARAN TRAINER TV DIGITAL PADA MATA PELAJARAN PENERAPAN SISTEM RADIO DAN TELEVISI DI KELAS XI TEKNIK AUDIO VIDEO SMK NEGERI 3 SINGARAJA - Dewa Nyoman Widiana Nida; Agus Adiarta; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
This study aims to design and create a Digital TV Trainer media, determine the media as a support for the learning process, and determine the response of students to the media in the subject of Radio and Television System Application in the Audio Video Engineering Expertise Program (TAV). This research includes the R&D (Research and Development) research model. The study used a questionnaire or questionnaire as an instrument of data collection by content experts, media experts, and students. From the research results obtained: the results of the expert trial obtained a value of 93.18% with a very decent classification, the results of the media expert trial obtained a percentage of 92.04% with a very decent classification, the results of the small group test the results of the lowest respondent score with a score of 52 classifications is very good, the results of the large group test result in the lowest respondent's score with a score of 52 including very good classification. Results Based on the research, the Digital TV Trainer media was designed and made suitable for use in the learning process of the subject of Radio and Television System Application in the Audio Video (TAV) Expertise Program at SMK Negeri 3 Singaraja.